2023
DOI: 10.1101/2023.01.10.523167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paresthesia during spinal cord stimulation depends on synchrony of dorsal column axon activation

Abstract: Spinal cord stimulation (SCS) reduces chronic pain. Conventional (40-60 Hz) SCS engages spinal inhibitory mechanisms by activating low-threshold mechanoreceptive afferents with axons in the dorsal columns (DCs). But activating DC axons typically causes a buzzing sensation (paresthesia) that can be uncomfortable. Kilohertz-frequency (1-10 kHz) SCS produces analgesia without paresthesia and is thought, therefore, not to activate DC axons, leaving its mechanism unclear. Here we show in rats that kilohertz-frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 113 publications
1
7
0
Order By: Relevance
“…This effect is not accounted for in our model, in which axons could continue to fire indefinitely in regular patterns, and it is a current limitation in the current gold standard MRG-based modeling approach. However, our results do predict that kilohertz-frequency SCS will produce bursts of action potentials at suprathreshold amplitudes (figure 8), which agrees with recent recordings during kilohertzfrequency stimulation by Sagalajev et al [60].…”
Section: Comparison Of Modeling Results With Existing Experimental Ev...supporting
confidence: 93%
See 4 more Smart Citations
“…This effect is not accounted for in our model, in which axons could continue to fire indefinitely in regular patterns, and it is a current limitation in the current gold standard MRG-based modeling approach. However, our results do predict that kilohertz-frequency SCS will produce bursts of action potentials at suprathreshold amplitudes (figure 8), which agrees with recent recordings during kilohertzfrequency stimulation by Sagalajev et al [60].…”
Section: Comparison Of Modeling Results With Existing Experimental Ev...supporting
confidence: 93%
“…Recent experiments have demonstrated that stimulating DC fibers at amplitudes just above activation threshold will produce asynchronous firing responses [68]. While deterministic fiber models provide qualitatively accurate approximations of the response to SCS, incorporating the stochastic ion channel properties produced results that demonstrated fluctuations in spike timing that more closely resemble experimental recordings [60,68].…”
Section: Effects Of Stochastic Ion Channelsmentioning
confidence: 96%
See 3 more Smart Citations